Module-based simulation model for prediction of convective and condensational heat recovery in a centrifugal wet scrubber. (25th January 2023) - Johansson, Wanja; Li, Jun; Lin, Leteng
Highlights: Heat recovering scrubber increases thermal efficiency of boiler with up to 20 %. Module-based simulation model on heat recovery has been developed and validated. The developed simulation model shows mean error of 5.6 % with low computation time. Evaporative cooling further increases heat recovery as predicted by the simulation. Abstract: Biomass combustion is a carbon–neutral method to generate heat and power and is integral to combating climate change. The wet scrubber is a promising device for recovering heat and reducing particle emissions from flue gas, under the driving force of new European Union legislation. Here, the heat recovery of a wet scrubber was investigated using process data and computer simulations. The process data showed that the scrubber could continuously recover heat corresponding to 10–20% of the energy input. The simulation model consists of two interlinked modules: Module 1 simulates droplet movement in the scrubber, while Module 2 uses the output of Module 1 to predict the heat recovery. The model was validated against process data, showing a mean error of 5.6%. Further optimization was based on the validated model by varying different process parameters, including nozzle position and moisture addition to the flue gas. Moisture addition was shown to be a feasible strategy for potentially increasing heat recovery by up to 3.3%. These results indicate that heat recovery in wet scrubbers is a feasible way to make particle removal cost effective in medium-scale combustion facilities, and that the developed simulation model can play an important role in optimizing these processes.